Answer:
f(8) = g(3)
Explanation:
f(x) = (x − 3)^2 + 4 and g(x) = x^3 + 2
We need to determine the values when we replace x
f(-2) = (-2 − 3)^2 + 4 = (-5)^2 +4 = 25+4 =29
f(0) = (0 − 3)^2 + 4 = (-3)^2 +4 = 9+4 = 13
f(2) = (2 − 3)^2 + 4 = (-1)^2 +4 = 1+4 =5
f(8) = (8 − 3)^2 + 4 = (5)^2 +4 = 25+4 =29
Now we find a g(x) value that matches one of these we are good
g(-3) =(-3)^3 + 2 = -27 +2 = -25
g(-1) = (-1)^3 + 2 = -1 +2 = 1
g(1) = (1)^3 + 2 = 1 +2 = 3
g(3) = (3)^3 + 2 = 27 +2 = 29
f(8) =29 and g(3) = 29
so f(8) = g(3)